Associations Between Noticing Nicotine Vaping Product Health Warning Labels, Harm Perceptions, and Use Among Adult Vapers, Current and Former Smokers. Findings From the 2018 ITC Four Country Smoking and Vaping Survey. Issue 7 (10th December 2021) - Taylor, Eve; Aleyan, Sarah; East, Katherine; Michael Cummings, K; Thrasher, James F; Fong, Geoffrey T; Quah, Anne C K; Li, Grace; Borland, Ron; Hammond, David; Hitchman, Sara C
Abstract: Background: The number of countries mandating a nicotine addiction warning label ("warnings") on nicotine vaping products (NVPs) has been increasing. This study examined associations between noticing NVP warnings, perceptions of NVPs, and intentions to use NVPs. Aim and Methods: Cross-sectional analysis of 12 619 adult NVP users, cigarette smokers, concurrent users of both cigarettes and NVPs, and quitters who participated in the 2018 International Tobacco Control (ITC) Project Four Country Smoking and Vaping Survey (England, Australia, Canada, USA). Logistic regression analyses examined associations between noticing warnings in the past 30 days and perceptions of nicotine harm, NVP harm relative to cigarettes, and NVP addictiveness relative to cigarettes. Associations were also explored between noticing warnings and intentions to use NVPs. Results: Noticing warnings was higher among NVP users (18.8%) than nonusers (2.1%). Noticing warnings was associated with perceiving nicotine to pose little or no harm to health among NVP users, but there was no association among nonusers. There was little evidence of an association between noticing warnings and perceptions of NVP harms relative to smoking among NVP users and non-users. Noticing warnings was associated with perceiving NVPs as less addictive than cigarettes among nonusers but not NVP users. Among exclusive smokers, noticing warnings was associated with intending to start using NVPs. Among NVP users, there was little evidence of an association between noticing warnings and intentions to continue using/stopping NVPs. Conclusions: Noticing NVP warnings was not associated with increased NVP and nicotine harm perceptions or decreased intentions to use NVPs among adult smokers and vapers. Implications: Our findings suggest that noticing NVP warnings may not influence NVP risk perceptions or deter NVP use among adult smokers and vapers. Future research should investigate the impact of warnings on youth and adults who have never smoked or vaped.